Effects of 1,3‐propanediol associated, or not, with butylene glycol and/or glycerol on skin hydration and skin barrier function - Pinto, Juliana Rodrigues; Monteiro e Silva, Silas Arandas; Leonardi, Gislaine Ricci (International journal of cosmetic science, 2024)
Objective This study aimed to assess the effect of 1,3‐propanediol at different concentrations (5%, 10%, or 15%), either applied alone or in combination with butylene glycol (BG) (5%) and/or glycerol (5%), on skin hydration and skin barrier function. The measurements were conducted using capacitance to determine skin hydration and trans epidermal water loss (TEWL) rates to evaluate skin barrier function. Methods A total of 30 healthy female subjects participated in the study. Capacitance and TEWL measurements were conducted at multiple time points, including before application and at 15 min, 2 and 8 h after the humectants were applied to the forearms of the subjects. All the subjects provided written informed consent. Results The 1,3‐propanediol in all concentrations and in all combinations (with BG and/or glycerol) increased skin hydration and improved skin barrier function 15 min, 2 and 8 h after application. Glycerol increased the hydration performance of 1,3‐propanediol. The application of 1,3‐propanediol at a concentration of 15%, either alone or in combination with other humectants, reduced the TEWL to a greater extent than lower concentrations of 1,3‐propanediol. Furthermore, the addition of glycerol to 1,3‐propanediol 15% improved the skin barrier and reduced TEWL when compared with 1,3‐propanediol alone and with the combination of 1,3‐propanediol + BG. Conclusion The humectants significantly improved skin hydration and reduced TEWL throughout the 8‐h time course. The increase in 1,3‐propanediol concentration, as well as its combination with glycerol, provided a greater benefit to the skin, improving both hydration and the skin barrier function. RÉSUMÉ OBJECTIF Cette étude visait à évaluer l’effet sur l’hydratation de la peau et la fonction de barrière cutanée du 1,3‐propanediol à différentes concentrations (5 %, 10 % ou 15 %), appliqué seul ou en association avec du butylène glycol (5 %) et/ou du glycérol (5 %). Les mesures ont été effectuées à l’aide de la capacitance pour déterminer l’hydratation de la peau et les taux de perte d’eau transépidermique (Trans Epidermal Water Loss, TEWL) pour évaluer la fonction de barrière cutanée. MÉTHODES Au total, 30 sujets de sexe féminin en bonne santé ont participé à l’étude. Les mesures de la capacitance et de la TEWL ont été effectuées à plusieurs moments, y compris avant l’application, 15 minutes, 2 heures et 8 heures après l’application des produits humectant sur les avant‐bras des sujets. Tous les sujets ont fourni un consentement éclairé écrit. RÉSULTATS Le 1,3‐propanediol, à toutes les concentrations et dans toutes les associations (avec le butylène glycol et/ou le glycérol), a augmenté l’hydratation de la peau et amélioré la fonction de barrière cutanée à 15 minutes, 2 heures et 8 heures après l’application. Le glycérol a augmenté les performances d’hydratation du 1,3‐propanediol. L’application de 1,3‐propanediol à une concentration de 15 %, seul ou en association avec d’autres produits humectant, a réduit la TEWL dans une plus grande mesure que des concentrations inférieures de 1,3‐propanediol. En outre, l’ajout de glycérol au 1,3‐propanediol 15 % a amélioré la barrière cutanée et réduit la TEWL par rapport au 1,3‐propanediol seul et à l’association 1,3‐propanediol + butylène glycol. CONCLUSION Les produits humectant ont significativement amélioré l’hydratation de la peau et réduit la TEWL tout au long des 8 heures. L’augmentation de la concentration de 1,3‐propanediol, ainsi que son association avec le glycérol, ont apporté un plus grand bénéfice à la peau, améliorant à la fois l’hydratation et la fonction de barrière cutanée. In this original paper we demonstrated that the increase in 1,3‐propanediol concentration, as well as its combination with glycerol, provided a greater benefit to the skin, improving both hydration and the skin barrier function.